Forecasting Postwar Demand: Discussion - Roos, Charles F.; Hurwicz, Leonid; Higgins, Benjamin; Koopmans, Tjalling; Hagen, Everett E.; Fuller, K. G.; Nienstaedt, L. R.; Marshak, Jacob (Econometrica, 1945)
Charles F. Roos, Leonid Hurwicz, Benjamin Higgins, Tjalling Koopmans, Everett E. Hagen, K. G. Fuller, L. R. Nienstaedt, Jacob Marshak, Forecasting Postwar Demand: Discussion, Econometrica, Vol. 13, No. 1 (Jan., 1945), pp. 54-59